Physical fitness assessment in wheelchair basketball: A mini-review - Luca Petrigna; Simona Pajaujiene; Giuseppe Musumeci; Giuseppe Musumeci; Giuseppe Musumeci (Frontiers Media S.A., 2022)
IntroductionWheelchair basketball (WB) is a Paralympic sport ideated for people with motor disabilities, and the research on this topic still requires attention. It is fundamental to evaluate physical fitness characteristics with appropriate tests and standardized routines to plan and monitor the training. Considering that a standard operating procedure is a document that makes the test battery replicable, the objective of the present study was to review the literature on physical fitness assessment in WB players and to create a standard operating procedure.MethodsStudies were collected from different databases, and after a screening process, data were discussed narratively.ResultsOnly 18 articles met the eligibility criteria. The test batteries presented similarities in different studies.ConclusionThe suggested standard operating procedure consists of 10-min warm-up followed by handgrip evaluation (only if the instrument is available), 20-m sprint test, maximal pass, modified push-up, back scratch test, and the Yo-Yo intermittent recovery test adapted test Version 1.